THE IMPORTANCE OF ENGLISH SKILL IN OPERATIONAL DEPARTMENTS IN HOTEL - Salma Permana, Michelle (Journal of Language Teaching Lingustics and Literature, 2023)
This study aims to analyze the level of the importance of  English  skill  in  operational  departments from the point of  view  of  a hotel  employee.  This  research  is qualitative research since the data obtained are in a form of  description  which is  in  non-numerical  data that focuses on the study of  meaning. The data are collected  through  questionnaire  with  closed ended questions. The research findings show that from seven English  skills,  there are four highest perceived importance    skills    to   have   as   an   operational department employee. They are listening skill, speaking skill, writing skill, and grammar in speaking skill.